George Rodger : an adventure in photography, 1908-1995 - Naggar, Carole, 1951- (Syracuse University Press, 2003)
He quit war photography when he realized he was arranging "thousands of Jewish corpses in nice photographic compositions." He went on to become a key photographer of African tribal life, covering over 75,000 miles of "old Africa" in a Land Rover and even surviving a white rhino charge."